The Lonely Girl. External Factors in the Conversion and Failed Ransom of the Turkish–Algerian Fatima (1608–1622) - Pomara Saverino, Bruno (Religions, 2023)
Research into various aspects of slavery and the related conversions has multiplied in recent years. This contribution investigates the case of Fatima, a young woman belonging to the Turkish–Algerian elite, who was captured in 1608 by the Tuscan Knights of Saint Stephen. Rescued by her parents and entrusted to some Corsican merchants for her safe return home, she remained in Calvi (Corsica) because she embraced Christianity. Thus, the local bishop pretended to keep her under his protection. Because of her conversion, her homecoming became considerably more complicated until it was decreed impracticable. The intervention of Fatima’s parents led to the opening of protracted negotiations between the political (Algerian, Ottoman, Spanish, Genoese) and ecclesiastical (Papal, Episcopal, Trinitarian) authorities. In dissatisfaction, the Algerian governors lashed out at one hundred and thirty Christian captives in Algiers whose rescue operation by Trinitarian redeemers was suddenly halted. Historiography, to narrate this case study, has paid attention predominantly to Spanish records and explained the political and economic mechanisms of the rescue machine with all its complications. Through other unpublished Spanish, Vatican and Genoese sources, this article focuses with a micro-glocal lens on the many psychological pressures used by political and religious agencies that accompanied such a young person by leveraging the decisive role of the Ecclesiastical authorities.